Consórcio de exportação de software: pequenas e médias empresas sob a perspectiva de redes sociais - Zacharias, Ana Paula de Lacerda (2009)
This work aims at verifying whether the organization in consortium collaborates to the export insertion of small and medium Brazilian software companies. The verification has been carried out from the social network perspective. It has made use of a qualitative methodology by means of a multi-case study whose target was the Actminds - a software export consortium located in Campinas - SP. For this purpose, social networks analyzing tools and metrics, such as centrality index and degree, have been employed. Results indicate that organization in consortiums is indeed a key factor for the export insertion of the studied companies.